Effect of Mocaf Flour Formulation (Modified Cassava Flour) and Wheat Flour with Various Cooking Methods ofthe Carbohydrate Levels of Bolu Kojo - Yani, Ade Vera; Idealistuti, Idealistuti; Maghfiroh, Nur Izzatul (Edible: Jurnal Penelitian Ilmu-ilmu Teknologi Pangan, 2023)
Bolu kojo is a cake originating from South Sumatra which is quite famous in the city of Palembang which has a dense and soft texture, and has a characteristic green color and is shped like a frangipani flower. This study aims to determine the effect of the formulation of mocaf flour and wheat flour with various cooking methods on the carbohydrate levels of bolu kojo. The method used was the experimental method with a Randomized Block Design (RBD) which consisted of two factors, namely the formulation of mocaf flour and wheat flour and various cooking methods with six sets of treatments and repeated three times. The observed effect factors were formulations of mocaf flour and wheat flour (=75% mocaf and 25% wheat), (=50% mocaf and 50% wheat) and (=25% mocaf and 75% wheat) and the cooking method ( = Baking) and ( = Steaming). The results showed that mocaf flour and wheat flour formulations with various cooking methods had a significant effect on carbohydrates. The highest carbohydrate value was found in the treatment with an average of 29.94%.